Error sensitivity analysis for multi-copter planar positioning on low-gain nearfield measurements - Pienaar, H.; Davidson, David (2016)
© 2016 IEEE. Near-field scanning using multi-copter based artificial sources could aid calibration of elemental patterns on large Mid Frequency Aperture Array (MFAA) stations, planned for phase 2 of the Square Kilometre Array (SKA) project. Current high-end positioning systems used on multi-copters have an accuracy in the order of centimetres. This study investigates the extent of errors caused by uncertainties in planar positioning during a near-field scan on wide field of view (FoV) antennas. It is found that at planar positioning accuracies of 1 cm, an upper bound far-field error of 10% at 450 MHz to 30 % at 1450 MHz can be expected.